2015
DOI: 10.17756/jrds.2015-003
|View full text |Cite
|
Sign up to set email alerts
|

Individualizing Opioid Use Disorder (OUD) Treatment: Time to Fully Embrace a Chronic Disease Model

Abstract: The current opioid epidemic in the United States is changing our perceptions of the face of addiction. Opioid Use Disorder (OUD) has become pervasive and is affecting all ethnicities, races, socioeconomic classes, the young and the old. In 2015, 46 people will lose their life each day to a chronic brain disease that is going unnoticed and undertreated. Over the last five decades, numerous scientific and clinical breakthroughs have allowed for a better understanding of the mechanisms underlying addiction, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…a number of variables are known to affect the recovery and ultimately treatment success [15]. In this context we agree with Gustin et al [1] that the treatment protocol should be individualized but the variables that affect the outcome are difficult to quantify. It is difficult to precisely predict the length of treatment a particular individual would need.…”
Section: Do We Really Need To Continue Pharmacotherapy For Opioid Usesupporting
confidence: 75%
See 2 more Smart Citations
“…a number of variables are known to affect the recovery and ultimately treatment success [15]. In this context we agree with Gustin et al [1] that the treatment protocol should be individualized but the variables that affect the outcome are difficult to quantify. It is difficult to precisely predict the length of treatment a particular individual would need.…”
Section: Do We Really Need To Continue Pharmacotherapy For Opioid Usesupporting
confidence: 75%
“…Of course there will be few patients that will never respond. Because a few patients will not respond to any length of treatment does not justify recommending long-term (lifelong) treatment protocol for all patients as suggested by Gustin et al [1].…”
Section: Do We Really Need To Continue Pharmacotherapy For Opioid Usementioning
confidence: 99%
See 1 more Smart Citation
“…Many individuals struggle with overcoming opioid abuse due to the intense withdrawal symptoms that occur when opioid use is discontinued that may include dysphoric mood, nausea or vomiting, fever, insomnia and/or muscle aches among others (American Psychiatric Association, 2013). Accordingly, relapse from opioid abstinence is common and makes the necessity for accessibility to OUD treatment vital for many to experience success in their recovery (Gustin et al, 2015; Martin et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Most authors have suggested that buprenorphine/naloxone should be utilized as a long-term opioid maintenance therapy based on the chronicity of opioid dependence (Gustin, Nichols, Martin, et al, 2015), while some others do not support this “mainstream” view (Badgaiyan, Sinha, Blum, 2015). …”
mentioning
confidence: 99%